Factors affecting the microbiological quality and contamination of farm bulk milk by Staphylococcus aureus in dairy farms in Asella, Ethiopia - Deddefo, A.; Mamo, G.; Asfaw, M.; Amenu, Kebede (Springer, 2023)
Background The determination of the microbiological quality and safety of raw milk and the associated influencing factors at the farm level is very critical given that the quality or safety of subsequent products that are further produced depends on this. Therefore, this study aimed to determine the microbiological quality and safety of bulk milk and identify associated risk factors, and assess the presence/absence of S. aureus in bulk milk with potential contaminating sources in dairy farms in Asella, Ethiopia.